The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/jnr.23507
|View full text |Cite
|
Sign up to set email alerts
|

Unique molecular signatures of Alzheimer's disease amyloid β peptide mutations and deletion during aggregate/oligomer/fibril formation

Abstract: The formation of amyloid β (Aβ) peptide aggregates, oligomers, and fibrils is a dynamic process; however, the kinetics of their formation is not well understood. This study compares the time course of aggregate/fibril formation by transmission electron microscopy (TEM) analyses with that of oligomer/fibril formation by Western blot analysis under native and denaturing conditions. Efforts to deaggregate/defibrillate these peptides by using hexafluoroisopropanol, ammonium hydroxide, or dimethylsulfoxide did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…Several groups have observed the opposite phenomena to our findings in experiments using synthetic peptides, showing that their own Osaka-mutant peptides promptly aggregated into amyloid fibrils [28][29][30][31][32][33][34][35]. However, we have often experienced that the aggregation property of synthetic peptides show remarkable lot-to-lot variations and that peptide aggregation largely depends on the experimental conditions, including the environment surrounding the peptides.…”
Section: Animal Modelscontrasting
confidence: 73%
“…Several groups have observed the opposite phenomena to our findings in experiments using synthetic peptides, showing that their own Osaka-mutant peptides promptly aggregated into amyloid fibrils [28][29][30][31][32][33][34][35]. However, we have often experienced that the aggregation property of synthetic peptides show remarkable lot-to-lot variations and that peptide aggregation largely depends on the experimental conditions, including the environment surrounding the peptides.…”
Section: Animal Modelscontrasting
confidence: 73%
“…In the present study, we observed a slight reduction in nuclear area and total neurite length (with no differences between the wt and mutant proteins) at non-physiological (14 µM) concentrations, however this is approximately 100 times higher than the EC 50 observed with either wt or mutant Aβ in the trafficking assay. show that A673T Aβ mutant aggregates are structurally distinct from wt aggregates (Benilova et al, 2014;Colombo et al, 2017;Lin et al, 2017;Murray et al, 2016;Poduslo & Howell, 2015;Zheng et al, 2015). This different shape could lead to binding to different receptors, which could account for lower synaptic affinity binding and/or increased toxicity of mutant protein oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar = 20 microns. Results were obtained from N = 4 independent neuronal culture experiments vitro (Benilova et al, 2014;Colombo et al, 2017;Lin et al, 2017;Maloney et al, 2014;Murray et al, 2016;Poduslo & Howell, 2015;Somavarapu et al, 2017). Many of these reports show that A673T…”
Section: Discussionmentioning
confidence: 99%
“…The next step in a process of Aβ aggregation is forming hydrogen bonds between the amide and the carbonyl (check spell) groups of anti-parallel oriented β-sheets with further aggregation into higher order structures (Poduslo and Howell, 2015 ). The aggregation of Aβ into fibrils is a complicated multi-step process that occurs through a number of intermediate structural forms and can be described as a sequential process consisting of several phases: monomers → misfolded monomers → soluble oligomers (clusters of small numbers of peptide molecules without a fibrillar structure) → protofibrils (aggregates of isolated or clustered spherical beads made up of ~20 molecules with β-sheet structure) → mature fibrils (Sengupta et al, 2014 ) (Figure 1 ).…”
Section: The Biophysics Of Aβ Aggregationmentioning
confidence: 99%